Fallen Angels - Myers, Walter Dean, frey50 (New York : Scholastic Inc., 1988)
Seventeen-year-old Richie Perry, just out of his Harlem high school, enlists in the Army in the summer of 1967 and spends a devastating year on active duty in Vietnam.
77871
Keywords: Vietnamese Conflict, 1961-1975 -- Fiction; African Americans -- Fiction